Political buzzers’ role on social media during the 2019 indonesian presidential election - Muhammad Budiana (Penerbit Universiti Kebangsaan Malaysia, 2024)
The 2019 presidential election involved political buzzers as one of the keys to the campaign on social media for both parties. The existence of the buzzers itself has a positive and negative impact on Indonesian society. Currently, the term “buzzers” have changed from a marketing function to a word that has a negative connotation because it is often identified with hoax news. This research uses qualitative methods, using literature studies from various documents, news, journals and previous research that are relevant to the role of buzzers in the spread of fake news on social media in the 2019 Presidential Election. After conducting searches and obtaining material that is relevant to the topic of analysis, this article analysed material and news developing in society regarding the role of buzzers in spreading hoaxes in the 2019 Presidential Election. The aim of the hoax campaign is to change the stigma from bad to good to increase electability and popularity, but it can also be the opposite, from good to bad. The 2019 presidential election noted that both parties were using them and at the same time were under attack from buzzers. One of the strategies used by buzzers during the 2019 Presidential Election is to normalise lies where both parties slander each other. The existence of a hoax campaign makes news about the Presidential Election confusing and needs to be checked carefully to ensure the facts of the news.